Prevalence of Nocturnal Frontal Lobe Epilepsy in the Adult Population of Bologna and Modena, Emilia-Romagna Region, Italy - Vignatelli, Luca (Sleep, 2015)
STUDY OBJECTIVES: To estimate the prevalence of nocturnal frontal lobe epilepsy (NFLE) in the adults of two areas of the Emilia-Romagna region (northeast Italy) and to describe the clinical features from a population-based perspective. DESIGN: Population-based retrospective cohort study including adults with NFLE. SETTING: Two areas of the Emilia-Romagna region: the city of Bologna (330,901 adult residents) and five districts of the province of Modena (424,007). Prevalence day: December 31, 2010. PARTICIPANTS: Patients with NFLE collected from multiple databases of neurologic hub centers of the districts involved. Diagnostic criteria: clinical history of sleep related bizarre motor attacks and videopolysomnographic recording confirming the typical features of NFLE. Inclusion criteria for prevalence calculation: residence in one of the two geographic areas on the prevalence day and an “active” or “in remission with treatment” form of NFLE. MEASUREMENTS AND RESULTS: Six subjects from Bologna and eight from Modena were included. Crude prevalence (per 100,000 residents) was 1.8 (95% confidence interval 0.7–4.0) in Bologna and 1.9 (0.8–3.7) in Modena. Similarly, the main clinical features were consistent: onset during adolescence (median age 11–13 y), mainly hyperkinetic seizures, nonlesional form in more than two-thirds of cases, an active form of epilepsy in more than two-thirds of cases. A family history of epilepsy was reported only for two patients. CONCLUSIONS: This epidemiologic study establishes that nocturnal frontal lobe epilepsy is a rare epileptic condition, fulfilling the definition for rare disease. Because of methodological limitations of our case ascertainment, the estimates we disclose must be considered the minimum prevalence. CITATION: Vignatelli L, Bisulli F, Giovannini G, Licchetta L, Naldi I, Mostacci B, Rubboli G, Provini F, Tinuper P, Meletti S. Prevalence of nocturnal frontal lobe epilepsy in the adult population of Bologna and Modena, Emilia-Romagna Region, Italy. SLEEP 2015;38(3):479–485.